The social cost of Environmental Pollution Causes and Enhancement options - Lubna Nameer Abid , Dr; Ahmed Kudhair Hussein, Dr. (lark, 2023)
The dilemma of environmental pollution is linked to the misuse and depletion of environmental resources in an irregular manner, causing them to lose their balance and increase their risks, which in turn affects the entire ecosystem in all its forms (air, water, soil). Even the unawareness or negligence in dealing with environmental resources by individuals or certain entities leads to significant pollution in the environment, impacting society and health. Environmental pollutants in Iraq are increasing due to political, security, and economic conditions, accompanied by the destruction of infrastructure as a result of wars and their aftermath, such as targeting power generation stations, economic facilities, industrial plants, railways, oil sources, sewage treatment and disposal systems, residential complexes, water filtration unit failures, and the limited role of waste transportation and disposal. All these factors and more have exacerbated the dilemma of environmental pollution. The issues of environmental degradation and pollution are more closely related to urban areas than other regions, perhaps due to considering urban areas as huge consumers of environmental resources (food, water, energy, etc.) due to their increasing population engaged in industrial, literary, artistic, political, commercial, administrative, and public service fields, leading to significant waste generation. Based on this basis, the objectives of this research are to shed light on understanding the motives and causes of environmental pollution, focusing on the dimensions of environmental pollution (air, water, soil) in order to assess the extent of damage. Additionally, it aims to identify the social and health costs resulting from environmental pollution and explore the best means and methods to mitigate the harm caused by environmental pollution.